The development and pilot testing of a fall prevention education intervention for older persons at high risk of falls in a Malaysian primary care setting / Annaletchumy Loganathan - Annaletchumy, Loganathan (2018)
The aim of this study was to develop and pilot test a fall prevention education intervention for older persons with a high risk of falls in a primary care setting. There were three phases in this study. In the needs assessment study, the needs of community-dwelling older persons with a high risk of falls and healthcare professionals (HCPs) who managed falls were explored using qualitative interviews. The study was conducted at University Malaya Medical Centre (UMMC), Kuala Lumpur from July 2012 to April 2013. Semi-structured topical guides were developed to facilitate the interviews. The transcribed interview data were analysed thematically using Weft QDA. A systematic literature review was conducted to determine the effectiveness of FPEIs. The intervention was developed based on the evidence from the findings of the needs assessment, systematic review, theories and clinical practice guidelines. The Multifaceted Fall Education by Interprofessional Team (MuFE_IT) intervention consists of presentations by inter-professional team and a fall prevention education booklet. The MuFE_IT was then pilot-tested in three group sessions and revised based on the feedback from the participants. The study participants’ knowledge and behavioural changes were evaluated using questionnaires and focus-group discussions immediately, one-month, and three-month post-intervention. The data were analysed using SPSS and Weft QDA. In the needs assessment study, both the HCPs and older persons highlighted the need for educational materials on fall prevention. HCPs perceived their roles as the iv coordinator of care and provider of advice on fall prevention to older persons. HCPs were aware that they needed to consider older persons’ views, beliefs and behaviours when offering fall prevention advice. A systematic literature review of 21 RCTs found that FPEIs which involved HCPs in providing fall advice, educational pamphlets, small group sessions, video and multimedia presentations were effective. In the qualitative evaluation of the MuFE_IT, four themes emerged: change of attitude towards fall prevention, actions taken related to fall prevention, barriers in MuFE_IT implementation, and reasons to take action to prevent falls. The participants were more ‘careful’, ‘compliant’ and ‘motivated’ to prevent falls. The participants found the following components of the MUFE_IT intervention useful: professional advice from the presentation on proper shoe wear, medication review and home interior modification; information from the education booklet on fall prevention activities such as exercises; small discussion groups that eased interaction and allowed information to be shared among the participants. However, a few participants perceived that the advice given at the MuFE_IT intervention was ‘common sense’ and ‘not practical’, as these participants were already practising fall prevention activities. In addition, there was no improvement in their knowledge after attending the MuFE_IT intervention sessions. This study confirms the feasibility of developing an FPEI for older persons based on needs, evidence and theories using mixed research methods. The MuFE_IT warrants further study to evaluate its effectiveness in preventing falls in the Malaysian primary care setting.